Treatment of Pulmonary Vasculitis - Terrier, Benjamin; Guillevin, Loïc (Seminars in Respiratory and Critical Care Medicine, 2018)
Pulmonary vasculitis can be heterogeneous and have some pathophysiological, clinical, and biological specificities that might influence treatment choices. Main vasculitides associated with pulmonary vasculitis include antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis, immune complex small vessel vasculitis, and antiglomerular basement membrane disease. Patient characteristics and association of lung involvement with other manifestations affecting disease severity may also influence treatment strategy. Alveolar hemorrhage frequently requires urgent treatment to control the underlying disease and provide supportive care such as mechanical ventilation. The level of evidence of each treatment strategy varies according to the underlying disease, but treatment is usually based on a combination of glucocorticoids and immunosuppressive agents, especially cyclophosphamide and rituximab. The role of plasma exchanges, widely used in patients with severe vasculitis, is controversial, based on results from recent prospective randomized controlled trials.
Keywords: glucocorticoids; cyclophosphamide; rituximab; plasma exchanges; vasculitis; pulmonary vasculitis